(untitled) (Sains Humanika, 2014)
The present paper aims to identify mathematical thinking and physics achievement of secondary school students in Johor Bahru Malaysia. A total of 127 Form 4 students were selected from 3 Cluster Schools in Johor Bahru by using cluster sampling. This quantitative study used both test items and questionnaire for data collection. Cronbach’s alpha was run on a sample of 12 students and the overall reliability coefficient for both mathematical thinking and physics test was 0.865 and 0.867 respectively. Descriptive analysis was used to obtain data on students’ demographic information while inferential analysis was used to examine the relationship between mathematical thinking and physics achievement of the respondents. Findings showed significant relationship between all mathematical thinking skills and physics achievement. However, findings indicated that there was no significant difference in mathematical thinking and physics achievement by gender. In addition, the influence of mathematical thinking skills on students’ physics achievement was statistically significant with F (4,122) = 18.678, p < 0.001. In future study, it is suggested to have more sub-constructs of mathematical thinking and a heterogeneous sample with larger size to gain meaningful knowledge about mathematical thinking and physics achievement, thus paving the way for effective instructional activities.